Results of aortocoronary bypass operations. Follow-up in 343 patients. Issue 11 (November 1978) - Donaldson, R M; Honey, M; Sturridge, M F; Wright, J E; Balcon, R
Abstract : Three hundred and forty-three patients who had aortocoronary bypass graft operations for disabling angina were followed up for from 6 months to 5 years (average 2 years). 80 per cent had multiple grafts and 20 per cent had additional endarterectomy. The overall mortality within one month of operation was 5 per cent, and in those who had vein graft procedures only was 4 per cent. 11 per cent had a postoperative myocardial infarction (6% perioperative) and there were 3 per cent late deaths. At 3 years 90 per cent are surviving. 80 per cent are asymptomatic without treatment. The mean angina grade was 0.3 at the latest follow-up, compared with 2.5 before operation; maximum exercise tolerance was also significantly improved (P less than 0.001). When angina recurred, it did so in 80 per cent of the cases within 12 months of operation and was usually attributable to inadequate revascularisation. Ventricular function as assessed by preoperative ventriculography was the factor most clearly related to survival rate and the early excellent results of coronary bypass operations seem to be maintained up to 5 years. It is, therefore, reasonable to continue to advise operation if only for relief of angina.